Peningkatan Keterampilan Proses Sains dan Hasil Belajar Siswa melalui Model Pembelajaran Jelajah Alam Sekitar (JAS) - Ali Imran; Ida Royani; Masiah Masiah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The background of this study is to utilize the school environment as a learning medium to implement innovative learning processes and shape students' character, that learning can be done anywhere and anytime as long as it follows the existing learning system references. The purpose of this study is to improve science process skills and student learning outcomes through a learning model of exploring the environment. The type of research used is Class Action Research (PTK). This research was carried out in class XD with a total of 30 students. Data analysis techniques use quantitative and qualitative analysis techniques. The results of the research from cycle I to cycle II of students' science process skills in the observing aspect increased with the very good category, the classification aspect with the good category, the predictive aspect with the good category, the concluding aspect with the very good category, and the communication aspect with the very good category. The learning outcomes of students in the first cycle were obtained by 11 students who did not reach the KKM >70, and in the second cycle 4 people. Thus, it can be concluded that the Exploring the Environment (JAS) learning model can improve science process skills and student learning outcomes.